Forecasting the Exchange Rates of the Iraqi Dinar against the US Dollar using the Time Series model (ARIMA) - Dr. Alaa Kadhim Farhan; Mstfa Rasool Fakhir (International Journal of Engineering and Management Research, 2019)
Estimating the exchange rate is considered a key tool for economic planning and reaching economic stability. This study aims to reach the best model for predicting exchange rates of Iraqi Dinar against the U.S. dollar in the period (2008-2017). For this purpose the following methods have been adopted: - Time-series analysis using the Box – Jenkins approach. Forecasts obtained from the two models were compared using both mean of the absolute values of the errors (MAE) and the square root of the mean square error (RMSE). The ARIMA (1,1,1) model produced the best forecasts and it can be used as a reliable method of estimating the exchange rate of any foreign currency.